Adenosine Receptors in Neurology and Psychiatry - Mori, Akihisa, 1970- (International review of neurobiology ;, 2014)
This well-established international series examines major areas of basic and clinical research within neuroscience, as well as emerging and promising subfields. This volume concentrates on adenosine receptor science, providing insights useful for actual drug discovery/development in neurology and psychiatry areas.